Current evidence on the transmissibility of chronic wasting disease prions to humans—A systematic review. Issue 1 (30th January 2017) - Waddell, L.; Greig, J.; Mascarenhas, M.; Otten, A.; Corrin, T.; Hierlihy, K.
Summary: A number of prion diseases affect humans, including Creutzfeldt–Jakob disease; most of these are due to genetic mutations in the affected individual and occur sporadically, but some result from transmission of prion proteins from external sources. Of the known animal prion diseases, only bovine spongiform encephalopathy prions have been shown to be transmissible from animals to humans under non‐experimental conditions. Chronic wasting disease (CWD) is a prion disease that affects cervids (e.g., deer and elk) in North America and isolated populations in Korea and Europe. Systematic review methodology was used to identify, select, critically appraise and analyse data from relevant research. Studies were evaluated for adherence to good conduct based on their study design following the Cochrane collaboration's approach to grading the quality of evidence and the strength of recommendations (GRADE). Twenty‐three studies were included after screening 800 citations from the literature search and evaluating 78 full papers. Studies examined the transmissibility of CWD prions to humans using epidemiological study design, in vitro and in vivo experiments. Five epidemiological studies, two studies on macaques and seven studies on humanized transgenic mice provided no evidence to support the possibility of transmission of CWD prions to humans. Ongoing surveillance in the United States and Canada has not documented CWD transmission to humans. However, two studies on squirrel monkeys provided evidence that transmission of CWD prions resulting in prion disease is possible in these monkeys under experimental conditions and seven in vitro experiments provided evidence that CWD prions can convert human prion protein to a misfolded state. Therefore, future discovery of CWD transmission to humans cannot be entirely ruled out on the basis of current studies, particularly in the light of possible decades‐long incubation periods for CWD prions in humans. It would be prudent to continue CWD research and epidemiologic surveillance, exercise caution when handling potentially contaminated material and explore CWD management opportunities.